2011
DOI: 10.1007/s12471-011-0224-z
|View full text |Cite
|
Sign up to set email alerts
|

Patients with aortic stenosis referred for TAVI: treatment decision, in-hospital outcome and determinants of survival

Abstract: AimsTo assess treatment decision and outcome in patients referred for transcatheter aortic valve implantation (TAVI) in addition to predictive factors of mortality after TAVI.MethodsThree-centre prospective observational study including 358 patients. Endpoints were defined according to the Valve Academic Research Consortium.ResultsOf the 358 patients referred for TAVI, TAVI was performed in 235 patients (65%), surgical aortic valve replacement (AVR) in 24 (7%) and medical therapy (MT) in 99 (28%). Reasons to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 24 publications
4
23
0
Order By: Relevance
“…In the present study, advanced CKD was associated with worse outcomes (mortality, bleeding, and stroke) in high‐risk TAVR patients. This is in line with previous studies demonstrating that advanced CKD is an independent risk factor for mortality, stroke, and bleeding events in TAVR patients . The findings herein corroborate these earlier reports and the observation that mortality, bleeding events, and stroke cluster in this cohort.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, advanced CKD was associated with worse outcomes (mortality, bleeding, and stroke) in high‐risk TAVR patients. This is in line with previous studies demonstrating that advanced CKD is an independent risk factor for mortality, stroke, and bleeding events in TAVR patients . The findings herein corroborate these earlier reports and the observation that mortality, bleeding events, and stroke cluster in this cohort.…”
Section: Discussionsupporting
confidence: 93%
“…Patients who are referred for TAVI are older and, therefore, more often have associated cardiac and noncardiac chronic disease or comorbid conditions, which both may explain a higher prevalence of anemia in these patients. 4,28,29 In accordance with 4 previous studies that reported the cause or determinants of anemia in patients with heart disease, we found kidney impairment and peripheral vascular disease to be related to preoperative anemia. 7,12,15,30 These and almost all other factors associated with anemia in the present analysis are common in patients with anemia and frequently seen in patients who currently undergo TAVI.…”
Section: Prevalence and Factors Associated With Anemiasupporting
confidence: 91%
“…16 All procedures were performed under local or general anesthesia using the Medtronic CoreValve System (valve sizes 23,26,29, and 31 mm), the Edwards SAPIEN or SAPIEN XT Valve (valve sizes 23,26, and 29 mm), or the Direct Flow Valve (valve sizes 24 and 25 mm). After TAVI, antiplatelet therapy consisted of clopidogrel 75 mg for 6 months and aspirin 80 to 100 mg indefinitely.…”
Section: Methodsmentioning
confidence: 99%
“…According to our results, both logistic EuroSCORE and EuroSCORE II could be used as scoring systems for prediction of annual mortality or incidence of standardized combined endpoints following TAVI but with limited sensitivity and specificity. So far, papers using standardized endpoints defined according to VARC [11] that will enable a comparison of individual studies in the future have been published only sporadically [21].…”
Section: Discussionmentioning
confidence: 99%